Chapter 4 Six Steps for Constructing Composite Narratives (Taylor & Francis, 2024)
This book provides the first instructional guide to composite narrative research methods. Composite narratives are short vignettes that weave together quotes from multiple participants. The effect is to convey meaning to both academics and end-users, disseminating research findings succinctly and effectively. Readers interested in writing composite narratives will find a complete guide in this book. More and more researchers are using composite narratives to present their research findings, with support for the effectiveness of composite narratives as a research method growing. Inside this book, there is a rationale for why to use composite narratives and a complete guide for how to write them. Many examples from the author are provided, complete with audit trails that evidence how the composite narratives were written from the raw qualitative research data. Social science researchers at all career stages will be able to use this book to justify and construct composite narratives. Beginning with a discussion of this background, the proposed book will offer research students, supervisors, and experienced academics a manual for how and why to use composite narratives in social sciences research. The intended audience includes qualitative researchers in the social sciences.